Groundwater recharge estimation in relation to land use type and soil: the case of Hormat-Golina sub-basin, northern Ethiopia - Bezabih Kidane, Seyoum; Melkam Taye, Mariye (Frontiers in Water, 2025)
Water is a vital resource for humanity, with groundwater being the largest source of fresh water available. The Hormat-Golina sub-basin, located in the North Wollo Zone of the Amhara region, is a key area for groundwater-based irrigation. However, irregular rainfall patterns in both timing and distribution make it challenging for residents to maintain adequate soil moisture for crop growth. As a result, there is an increasing demand for agricultural development utilizing groundwater in this region. Despite ambitious irrigation expansion plans, there has been insufficient assessment of groundwater reserves and recharge rates. Understanding the spatial variability of groundwater recharge in relation to land use, soil texture, topography, groundwater levels, and hydrometeorological factors is crucial to ensure the sustainable development of groundwater resources. This study aimed to estimate the spatial groundwater recharge in the Hormat-Golina sub-basin in northern Ethiopia using a spatially distributed water balance model (WetSpass). Input data for the model were organized into grid maps with a 30 m grid size, and parameters were tailored to reflect the specific conditions of the sub-basin based on expert insights and scientific research. The model results demonstrated a strong correlation between observed and simulated surface runoff, with R2 = 0.94 and NSE = 0.85. The findings indicated that the long-term average annual rainfall of 829 mm was distributed as follows: 156 mm (19%) for surface runoff, 617 mm (73%) for evapotranspiration, and 55 mm (8%) for recharge. This recharge amounts to ~400,000 cubic meters for the Hormat-Golina sub-basin, which covers an area of about 698 km2. Notably, 83% of this recharge occurs during the rainy summer season, while the remaining 17% occurs during the dry (beg) season. The highest recharge rates were recorded in forested areas with sandy soil.